Thai Hoa palace’s decorative sculpture art in Hue Imperial city - Tran, Nam Thanh; Pham, Linh Nhu (Edelweiss Applied Science and Technology, 2025)
Built in 1805 during the reign of King Gia Long, the final feudal dynasty in Vietnam, Thai Hoa Palace is the most significant structure in Hue Imperial City and the site of important Nguyen Dynasty rituals. Early in the 19th century, talented craftspeople and builders from all across Vietnam constructed this structure. The palace was built in the extremely distinctive Hue architectural style known as "double roof, duplex house" or "overlap beam, double roof" (Trùng thiềm, Điệp ốc/ Trùng lương, Trùng thiềm). The palace includes two interconnected residences. Each house has two overlapping roofs, without ceilings, exposing the carved and overlapping wooden beams. Thai Hoa Palace is also ornately embellished with stone sculptures, enamel, and porcelain inlays. The palace's decorative art has its own unique style and inventiveness because it combines traditional Vietnamese decorative art with the best elements of modern external fine arts. Currently, Thai Hoa Palace is housed within the complex of Hue's old capital remains, which have exceptional worldwide artistic worth in their carving and mosaic ornamentation.